Simultaneous Decontamination for Ammonia Nitrogen and Phosphate Efficiently by Crystal Morphology MgO-Coated Functional Biochar Derived from Sludge and Sunflower Stalk - Zhiwei Li; Jingxin Huang; Weizhen Zhang; Hao Yu; Yin Wang (Toxics, 2025)
Eutrophication driven by nitrogen and phosphorus discharge remains a critical global environmental challenge. This study developed a sustainable strategy for synergistic nutrient removal and recovery by fabricating MgO-coated biochar (Mg-MBC600) through co-pyrolysis of municipal sludge and sunflower stalk (300–700 °C). Systematic investigations revealed temperature-dependent adsorption performance, with optimal nutrient removal achieved at 600 °C pyrolysis. The Mg-MBC600 composite exhibited enhanced physicochemical properties, including a specific surface area of 156.08 m2/g and pore volume of 0.1829 cm3/g, attributable to magnesium-induced structural modifications. Advanced characterization confirmed the homogeneous dispersion of MgO nanoparticles (~50 nm) across carbon matrices, forming active sites for chemisorption via electron-sharing interactions. The maximum adsorption capacities of Mg-MBC600 for nitrogen and phosphorus reached 84.92 mg/L and 182.27 mg/L, respectively. Adsorption kinetics adhered to the pseudo-second-order model, indicating rate-limiting chemical bonding mechanisms. Equilibrium studies demonstrated hybrid monolayer–multilayer adsorption. Solution pH exerted dual-phase control: acidic conditions (pH 3–5) favored phosphate removal through Mg3(PO4)2 precipitation, while neutral–alkaline conditions (pH 7–8) promoted NH4+ adsorption via MgNH4PO4 crystallization. XPS analysis verified that MgO-mediated chemical precipitation and surface complexation dominated nutrient immobilization. This approach establishes a circular economy framework by converting waste biomass into multifunctional adsorbents, simultaneously addressing sludge management challenges and enabling eco-friendly wastewater remediation.